Intestinal Behcet’s syndrome with an unusual complication bladder-intestines fistula and urinary tract infections—A case report - Deng, Jiewen; Fan, Xuanming; Guo, Hui; Gao, Jie; Li, Xuan; Wan, Wei (Frontiers in Cellular and Infection Microbiology, 2023)
A 33-year-old male patient with a 17-year Behcet’s syndrome history showed abdominal pain and fever symptoms. The abdominal CT was suggestive of an acute ileocecal intestinal perforation. In addition, the symptoms disappeared after the conservative treatment. Some related examinations, including capsule endoscopy, were performed to explain the phenomenon of the food residue urine. These results indicated the intestine-urinary tract fistula formation, supposed to be the outcome of intestinal Behcet’s syndrome perforation. This is a rare case of intestinal Behcet’s syndrome with abdominal symptoms as the main manifestation. It was complicated by entero-urinary fistula formation and urinary tract infections. Now, we report this story to emphasize that capsule endoscopy is conducive to the diagnosis and assessment of the intestinal Behcet’s syndrome; moreover, anti-inflammatory treatment including biological agents is effective to relieve the disease at the acute stage in addition to surgical methods.